REVITALISASI JARINGAN IRIGASI RAWA SUB-SEKUNDER UNTUK MENINGKATKAN PRODUKTIFITAS HASIL PERTANIAN (STUDI KASUS IRIGASI SUB-SEKUNDER RAWA PITU SP 2) - Arifaini, Nur; Zakaria, Ahmad; Setiawan, Randy (UNIVERSITAS LAMPUNG, 2014)
Lampung Province has a fairly wide swamp area, one of them is in Rawa Pitu area. Swamp irri- gation in Rawa Pitu area has not been used extensively. The purpose of this research is to conduct a study, analysis, and systematically arranged recommendations on revitalizing Rawa Pitu swamp area that can be optimized to increase food crops production in order to improve the welfare of society. The research site is located in the sub-district of Rawa Pitu, Tulang Bawang regency. The location of Rawa Pitu is between the Tulang Bawang and the Pidada rivers. Analysis in this study is more focused on the revitalization of the sub-secondary of swamp irrigation system to increase agricultural productivity in Rawa Pitu area by comparing before and after revitalization. From the calculation, it is obtained that: the maximum of 3 days cumulative daily rainfall with the 5 years return period is obtained 104,12 mm and the amount of drainage modulus is obtained at 4,016 mm / day. Agricultural yield before revitalized, for the rice, the profit is Rp.13.697.819.386,- and for the crops, the profit is Rp.12.452.563.078.-. Agricultural production after revitalized is in- crease, for the rice, the profit is Rp.18.739.594.819,- and for the crops, the profit is Rp.17.035.995.290,-. The value of benefit cost ratio is about 1,38 and it is greater than 1,0, so that there is a profit, and net present value is positive, it is Rp.7.642.988.768,-.